(untitled) (Research, Society and Development, 2022)
Objective: To analyze the morbidity and mortality profile of typhoid and paratyphoid fever and its relationship with basic sanitation services in Brazil, from 2010 to 2021. Methods: An observational study of the incidence rate and hospitalizations for typhoid and paratyphoid fever and socioeconomic characteristics, sanitation and health in Brazil. Results: There was a decrease in incidence and hospitalization in the analyzed period, however, the prevalence and higher rates in the North (4.7/100mil and 7.4/100mil) and Northeast (0.4/100mil and 4.7/100mil) - Amapá, Pará, Amazonas and Maranhão. With regard to socioeconomic aspects, there was low schooling in the country (1-10 years), income (R580-R1,026) and human development (0.631-0.690) in the North and Northeast; low health, home visit coverage (33.7%-42.3%) and incipient basic sanitation in all states, especially in the area of sanitation and, to this, there was a minimum investment per m² and higher spending on hospitalizations, especially in the Southeast and Northeast. The profile of the affected, higher frequency in men and age group of 15-39 years. Conclusion: The scenario of vulnerability of Brazilians to typhoid and paratyphoid fever is inferred, especially due to precariousness and lower investment in basic sanitation and, consequently, the maintenance of incidence rates and hospitalizations.